THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN THE DEVELOPMENT OF PEDAGOGICAL SCIENCE - Mamadjanova Mokhimir Rashidovna (Journals Park Publishing, 2023)
This article shows the effective aspects of the use of innovative methods in pedagogical activity, the process of integration between disciplines, the possibilities of information and communication technologies in creation of innovative methods.
Keywords: Method, innovation, innovative activity, innovative environment, pedagogical innovation, integration, quality, result.